The Triassic Mercia Mudstone Group: Sealing the UK's net zero future - Jonathon A. McEvoy; Richard H. Worden; Joshua Griffiths; Nicholas T. Smith; Daniel R. Faulkner; Samuel T.J. Jones; Holly J. Mills; Kevin G. Taylor (Earth-Science Reviews, 2026)

Rewilding reshapes gut microbiomes and parasite exposure in European bison: a 17‑month release from Wilder Blean - William JS Edwards; Yaseen Majid Salman Al-Adilee; Constance Denoyelle; Hannah Mackins; Richard A. Griffiths; Anastasios D. Tsaousis (Journal for Nature Conservation, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Naïve young Homing pigeons (Columba livia) learn efficient routes home but are not tied to those routes. - Sarah Stachowski; Charles Bishop; Charlotte Griffiths; Richard A. Holland (Behavioural Processes, 2026)

Factors influencing species reintroduction success - Gemma Harding; Richard A. Griffiths; Simon A. Black (Biodiversity and Conservation, 2025)
Conservation reintroductions are widespread in species conservation but evaluation of their success, and particularly the reporting of failures is lacking. Here we evaluate aspects of species reintroduction that influence success and how conservation practitioners measure success. We analysed trends and reasons for perceived failure and success across 341 documented reintroduction case studies from across the globe. Reintroductions in Africa had lower scores for success compared to East Europe, North & Central Asia; fish had higher scores than invertebrates; and government and non-government organisations scored projects as more successful than did zoos or aquaria. Goals and Indicators do not appear to influence the success score, although too many goals may have a negative influence on success. Qualitative analysis of the reasons for failure and success showed that activities linked to Partnerships & Support (e.g. community support, government partnerships) were the most regularly cited reason for success, and Habitat & Release site (e.g. poor habitat connectivity, lack of suitable release sites) were the most frequently cited reason linked to failure, or failed elements. Current conservation efforts continue to comprise a disproportionately high number of reintroductions for mammals and birds compared to other taxa, and the number of reintroductions in developed countries outweigh those of developing countries.

Large connected components in sexual networks and their role in HIV transmission in Sub-Saharan Africa: A model-based analysis of HPTN 071(PopART) data - Francesco Di Lauro; William J.M. Probert; Michael Pickles; Anne Cori; Robert Hinch; Luca Ferretti; Jasmina Panovska-Griffiths; Lucie Abeler-Dörner; Rory Dunbar; Peter Bock; Deborah J. Donnell; Helen Ayles; et al. (Journal of Theoretical Biology, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Natural history traits influence winners and losers for herpetological communities in disturbed tropical habitats - Rowland K. Griffin; Todd R. Lewis; Joseph Tzanopoulos; Richard A. Griffiths (Oecologia, 2025)
Habitat alteration can lead to a few ‘winning’ species outcompeting many ‘losing’ species, an effect commonly termed as ‘Winner-Loser-Replacements’ or WLRs. This can lead to homogenisation of species assemblages at phylogenetic and functional levels. Most previous studies analyse responses of species abundance without considering natural history traits associated with those species. This study uses fourth corner modelling techniques to investigate the interaction between ecological data and natural history trait information using a herpetofaunal assemblage that includes 19 species of amphibians, 28 snakes, and 20 lizards, in Parque Nacional Laguna del Tigre, Guatemala. A total of 120 transects were surveyed using Visual Encounter Surveys, comprising 18 in disturbed habitat, 66 in forest habitat, and 36 in edge habitat respectively. Overall, greater diversity of ecological traits was revealed in forest and edge habitats compared to disturbed habitats at the forest edge close to agricultural land. Models revealed that for amphibians ( Hypopachus variolosus and Incilius valliceps ) and snakes ( Coniophanes schmidtii and Leptodeira septentrionalis ), association with bare ground, and in the case of amphibians, leaf litter, predicts species persistence in disturbed habitats. Continued forest fragmentation in the region will result in increased edge effects, and a greater proportion of forest remaining in an early successional state, leading to a highly reduced, homogenized, amphibian and reptile assemblage. Using such models for community assemblages of animals to reveal the identity of WLR patterns in forests with continued fragmentation is a useful tool to reveal which species are at risk of impact before habitats become degraded.

Evaluating the effectiveness of seabird bycatch mitigation measures for pelagic longlines in the South Atlantic - James B. Bell; Johannes H. Fischer; Ana P.B. Carneiro; Shane Griffiths; Alessandra Bielli; Sebastián Jiménez; Steffen Oppel; Richard A. Phillips; Helen M. Wade; Oliver Yates; Stuart A. Reeves (Biological Conservation, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Genetic analysis of grain protein content and deviation in wheat - Rohan Richard; Alison Lovegrove; Paola Tosi; Richard Casebow; Mervin Poole; Luzie U. Wingen; Simon Griffiths; Peter R. Shewry (Journal of Cereal Science, 2025)

The legal and illegal supply chains of sea turtle eggs in Costa Rica - Helen Pheasey; Richard A. Griffiths; David L. Roberts (Environmental Development, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Wheat genetic resources have avoided disease pandemics, improved food security, and reduced environmental footprints: A review of historical impacts and future opportunities - Julie King; Susanne Dreisigacker; Matthew Reynolds; Anindya Bandyopadhyay; Hans‐Joachim Braun; Leonardo Crespo‐Herrera; Jose Crossa; Velu Govindan; Julio Huerta; Maria Itria Ibba; Carlos A. Robles‐Zazueta; Carolina Saint Pierre; et al. (Global Change Biology, 2024)
The use of plant genetic resources (PGR)—wild relatives, landraces, and isolated breeding gene pools—has had substantial impacts on wheat breeding for resistance to biotic and abiotic stresses, while increasing nutritional value, end‐use quality, and grain yield. In the Global South, post‐Green Revolution genetic yield gains are generally achieved with minimal additional inputs. As a result, production has increased, and millions of hectares of natural ecosystems have been spared. Without PGR‐derived disease resistance, fungicide use would have easily doubled, massively increasing selection pressure for fungicide resistance. It is estimated that in wheat, a billion liters of fungicide application have been avoided just since 2000. This review presents examples of successful use of PGR including the relentless battle against wheat rust epidemics/pandemics, defending against diseases that jump species barriers like blast, biofortification giving nutrient‐dense varieties and the use of novel genetic variation for improving polygenic traits like climate resilience. Crop breeding genepools urgently need to be diversified to increase yields across a range of environments (>200 Mha globally), under less predictable weather and biotic stress pressure, while increasing input use efficiency. Given that the ~0.8 m PGR in wheat collections worldwide are relatively untapped and massive impacts of the tiny fraction studied, larger scale screenings and introgression promise solutions to emerging challenges, facilitated by advanced phenomic and genomic tools. The first translocations in wheat to modify rhizosphere microbiome interaction (reducing biological nitrification, reducing greenhouse gases, and increasing nitrogen use efficiency) is a landmark proof of concept. Phenomics and next‐generation sequencing have already elucidated exotic haplotypes associated with biotic and complex abiotic traits now mainstreamed in breeding. Big data from decades of global yield trials can elucidate the benefits of PGR across environments. This kind of impact cannot be achieved without widescale sharing of germplasm and other breeding technologies through networks and public–private partnerships in a pre‐competitive space.

Neodymium isotope composition and rare earth element distribution of East Antarctic continental shelf and deep waters - Alex Griffiths; Myriam Lambelet; Kirsty Crocket; Richard Abell; Barry J. Coles; Katharina Kreissig; David Porter; Frank O. Nitsche; Mark Rehkämper; Tina van de Flierdt (Chemical Geology, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Performance of fur clips and livestock markers for identifying vaccinated badgers - Clare H. Benton; Amy L. Griffiths; Richard J. Delahay (European Journal of Wildlife Research, 2024)
Marking free-living wild mammals may be desirable during field studies and management interventions; however, doing so presents practical challenges. In the context of disease management interventions, different approaches such as vaccination and culling may be deployed in adjacent areas resulting in a need to identify previously vaccinated individuals to avoid losses of vaccination benefits. Badgers ( Meles meles ) have been identified as a wildlife reservoir of bovine tuberculosis in several countries. In England, the primary means of controlling disease in badger populations has been culling, although policy also includes the use of badger vaccination. Vaccination and culling can therefore increasingly take place in adjacent areas. The current means of marking vaccinated badgers is to apply a fur clip; however, the performance of this method has not been assessed. In this study, we assessed the field performance of livestock markers not previously trialled on badgers. We also assessed the performance of fur clips in terms of (a) how likely they are to be detected on recapture and (b) their detectability using remote cameras. None of the livestock markers trialled persisted well on badger fur. Detectability of fur clips on re-captured badgers fell to 50% in adult badgers by approximately 3 months from application. In cubs, detectability fell to less than 50% within 3 weeks of application. We suggest it is highly likely that, if vaccination and culling were carried out in adjacent areas and fur clipping was the primary means of determining vaccination status, a proportion of recently vaccinated badgers would be removed, particularly cubs. This has important implications for disease control, and we suggest options for minimising such losses.

Climate change disrupts the seasonal coupling of plant and soil microbial nutrient cycling in an alpine ecosystem - Arthur A. D. Broadbent; Lindsay K. Newbold; William J. Pritchard; Antonios Michas; Tim Goodall; Irene Cordero; Andrew Giunta; Helen S. K. Snell; Violette V. L. H. Pepper; Helen K. Grant; David X. Soto; Ruediger Kaufmann; et al. (Global Change Biology, 2024)
The seasonal coupling of plant and soil microbial nutrient demands is crucial for efficient ecosystem nutrient cycling and plant production, especially in strongly seasonal alpine ecosystems. Yet, how these seasonal nutrient cycling processes are modified by climate change and what the consequences are for nutrient loss and retention in alpine ecosystems remain unclear. Here, we explored how two pervasive climate change factors, reduced snow cover and shrub expansion, interactively modify the seasonal coupling of plant and soil microbial nitrogen (N) cycling in alpine grasslands, which are warming at double the rate of the global average. We found that the combination of reduced snow cover and shrub expansion disrupted the seasonal coupling of plant and soil N‐cycling, with pronounced effects in spring (shortly after snow melt) and autumn (at the onset of plant senescence). In combination, both climate change factors decreased plant organic N‐uptake by 70% and 82%, soil microbial biomass N by 19% and 38% and increased soil denitrifier abundances by 253% and 136% in spring and autumn, respectively. Shrub expansion also individually modified the seasonality of soil microbial community composition and stoichiometry towards more N‐limited conditions and slower nutrient cycling in spring and autumn. In winter, snow removal markedly reduced the fungal:bacterial biomass ratio, soil N pools and shifted bacterial community composition. Taken together, our findings suggest that interactions between climate change factors can disrupt the temporal coupling of plant and soil microbial N‐cycling processes in alpine grasslands. This could diminish the capacity of these globally widespread alpine ecosystems to retain N and support plant productivity under future climate change.

Restoring the seagrass Zostera muelleri with transplants: small cores are as effective as larger plots - Fleur E. Matheson; Graeme Mackay; Crispin Middleton; Richard Griffiths; Ricky Eyre; Josh Smith; Ron Ovenden (New Zealand Journal of Marine and Freshwater Research, 2023)
Seagrass extent has declined globally, including in New Zealand. Following the success of an initial trial to transplant and re‐establish intertidal seagrass at a former site in Whangarei Harbour, a second trial was initiated. This trial aimed to restore seagrass at a more distant former site and tested the efficacy of transplant units ranging in size from small cores (5 or 9 × 0.01 m diameter cores placed within a 0.25 m 2 plot) to larger entire plots (0.25 m 2 or 0.5 m 2 ). Seagrass was transplanted in winter when plants were dormant. Plant cover of transplanted and donor plots and light climate at both sites were monitored over a period of four years. All but one of the 24 units survived, and the plants began to spread after 12–18 months to eventually develop patches ranging in size from 5 to 68 m 2 . Seagrass recolonised all donor plots completely within 10 months. Results show that small cores and larger plots can both be used successfully to transplant and restore populations of Zostera muelleri with no long‐lasting damage to donor meadows. However, use of small cores is recommended to minimise extractions and loss of transplanted material, and to simplify logistics.

RiskScape: a flexible multi-hazard risk modelling engine - Ryan Paulik; Nick Horspool; Richard Woods; Nick Griffiths; Tim Beale; Christina Magill; Alec Wild; Benjamin Popovich; Glenn Walbran; Russel Garlick (Natural Hazards, 2023)
This paper presents the architecture and features of RiskScape software. RiskScape is an open-source software with a flexible modelling engine for multi-hazard risk analysis. The RiskScape engine implements modeller-defined risk quantification workflows as ‘model pipelines’. Model pipeline steps and functions analyse hazard, exposure, and vulnerability data across different spatio-temporal domains using geoprocessing and spatial sampling operations. The RiskScape engine supports deterministic and probabilistic risk quantification, with several probabilistic-based modes described in this paper. RiskScape advances modelling software for multi-hazard risk analysis through several implementation features. The RiskScape engine operates model pipelines independent of system prescribed model input data classifications or standards. Multiple hazard types, metric intensities, and temporal occurrence information is geometry processed and sampled to create coverage data of simultaneous or sequenced multi-hazard events at object-exposure locations. Escalating multi-hazard event impacts are then determined for object-exposures using scripted conditional or nested statements that apply vulnerability functions in a logical sequence of temporal hazard and impact occurrence. These model features, supported by open geospatial consortium standard geospatial data files and operations, expedite RiskScape for modelling multi-hazard risk at any geographical location or scale.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Whole-Ecosystem Warming Increases Plant-Available Nitrogen and Phosphorus in an Ombrotrophic Bog - Colleen M. Iversen; John Latimer; Deanne J. Brice; Joanne Childs; Holly M. Vander Stel; Camille E. Defrenne; Jake Graham; Natalie A. Griffiths; Avni Malhotra; Richard J. Norby; Keith C. Oleheiser; Jana R. Phillips; et al. (Ecosystems, 2023)

Diversity, fragmentation, and connectivity across the UK amphibian and reptile data management landscape - Rebecca K. Turner; Richard A. Griffiths; John W. Wilkinson; Angela M. Julian; Mike P. Toms; Nick J. B. Isaac (Biodiversity and Conservation, 2023)
Large-scale biodiversity monitoring remains a challenge in science and policy. ‘Biodiversity Observation Networks’ provide an integrated infrastructure for monitoring biodiversity through timely discovery, access, and re-use of data, but their establishment relies on an in-depth understanding of existing monitoring effort. We performed a scoping review and network analysis to assess the scope of available data on amphibians and reptiles in the UK and catalogue the mobilisation of information across the data landscape, thereby highlighting existing gaps. The monitoring portfolio has grown rapidly in recent decades, with over three times as many data sources than there are amphibian and reptile species in the UK now available. We identified 45 active sources of ‘FAIR’ (‘Findable’, ‘Accessible’, ‘Interoperable’ and ‘Reusable’) data. The taxonomic, geographic and temporal coverage of datasets appears largely uneven and no single source is currently suitable for producing robust multispecies assessments on large scales. A dynamic and patchy exchange of data occurs between different recording projects, recording communities and digital data platforms. The National Biodiversity Network Atlas is a highly connected source but the scope of its data (re-)use is potentially limited by insufficient accompanying metadata. The emerging complexity and fragmented nature of this dynamic data landscape is likely to grow without a concerted effort to integrate existing activities. The factors driving this complexity extend beyond the UK and to other facets of biodiversity. We recommend integration and greater stakeholder collaboration behind a coordinated infrastructure for data collection, storage and analysis, capable of delivering comprehensive assessments for large-scale biodiversity monitoring.

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Managing non-target wildlife mortality whilst using rodenticides to eradicate invasive rodents on islands - Paula A. Castaño; Karl J. Campbell; Greg S. Baxter; Victor Carrión; Francesca Cunninghame; Penny Fisher; Richard Griffiths; Chad C. Hanson; Gregg R. Howald; Wesley J. Jolley; Bradford S. Keitt; Pete J. McClelland; et al. (Biological Invasions, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Survival of climate warming through niche shifts: Evidence from frogs on tropical islands - Jim Labisko; Nancy Bunbury; Richard A. Griffiths; Jim J. Groombridge; Lindsay Chong‐Seng; Kay S. Bradfield; Jeffrey W. Streicher (Global Change Biology, 2022)
How will organisms cope when forced into warmer‐than‐preferred thermal environments? This is a key question facing our ability to monitor and manage biota as average annual temperatures increase, and is of particular concern for range‐limited terrestrial species unable to track their preferred climatic envelope. Being ectothermic, desiccation prone, and often spatially restricted, island‐inhabiting tropical amphibians exemplify this scenario. Pre‐Anthropocene case studies of how insular amphibian populations responded to the enforced occupation of warmer‐than‐ancestral habitats may add a valuable, but currently lacking, perspective. We studied a population of frogs from the Seychelles endemic family Sooglossidae which, due to historic sea‐level rise, have been forced to occupy a significantly warmer island (Praslin) than their ancestors and close living relatives. Evidence from thermal activity patterns, bioacoustics, body size distributions, and ancestral state estimations suggest that this population shifted its thermal niche in response to restricted opportunities for elevational dispersal. Relative to conspecifics, Praslin sooglossids also have divergent nuclear genotypes and call characters, a finding consistent with adaptation causing speciation in a novel thermal environment. Using an evolutionary perspective, our study reveals that some tropical amphibians have survived episodes of historic warming without the aid of dispersal and therefore may have the capacity to adapt to the currently warming climate. However, two otherwise co‐distributed sooglossid species are absent from Praslin, and the deep evolutionary divergence between the frogs on Praslin and their closest extant relatives (~8 million years) may have allowed for gradual thermal adaptation and speciation. Thus, local extinction is still a likely outcome for tropical frogs experiencing warming climates in the absence of dispersal corridors to thermal refugia.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Shrub expansion modulates belowground impacts of changing snow conditions in alpine grasslands - Arthur A. D. Broadbent; Michael Bahn; William J. Pritchard; Lindsay K. Newbold; Tim Goodall; Andrew Guinta; Helen S. K. Snell; Irene Cordero; Antonios Michas; Helen K. Grant; David X. Soto; Rüdiger Kaufmann; et al. (Ecology Letters, 2022)
Climate change is disproportionately impacting mountain ecosystems, leading to large reductions in winter snow cover, earlier spring snowmelt and widespread shrub expansion into alpine grasslands. Yet, the combined effects of shrub expansion and changing snow conditions on abiotic and biotic soil properties remains poorly understood. We used complementary field experiments to show that reduced snow cover and earlier snowmelt have effects on soil microbial communities and functioning that persist into summer. However, ericaceous shrub expansion modulates a number of these impacts and has stronger belowground effects than changing snow conditions. Ericaceous shrub expansion did not alter snow depth or snowmelt timing but did increase the abundance of ericoid mycorrhizal fungi and oligotrophic bacteria, which was linked to decreased soil respiration and nitrogen availability. Our findings suggest that changing winter snow conditions have cross‐seasonal impacts on soil properties, but shifts in vegetation can modulate belowground effects of future alpine climate change.

Nitrogen and phosphorus cycling in an ombrotrophic peatland: a benchmark for assessing change - Verity G. Salmon; Deanne J. Brice; Scott Bridgham; Joanne Childs; Jake Graham; Natalie A. Griffiths; Kirsten Hofmockel; Colleen M. Iversen; Terri M. Jicha; Randy K. Kolka; Joel E. Kostka; Avni Malhotra; et al. (Plant and Soil, 2021)

Multi-year analysis of aerosol optical properties and implications to radiative forcing over urban Pretoria, South Africa - Kanike Raghavendra Kumar; Richard Boiyo; Rehana Khan; Na Kang; Xingna Yu; Venkataraman Sivakumar; Derek Griffith; Nulu Latha Devi (Theoretical and Applied Climatology, 2020)

Risks posed by rat reproduction and diet to eradications on tropical islands - Araceli Samaniego; Richard Griffiths; Markus Gronwald; Nick D. Holmes; Steffen Oppel; Ben C. Stevenson; James C. Russell (Biological Invasions, 2020)

Using genetics to inform restoration and predict resilience in declining populations of a keystone marine sponge - Sarah M. Griffiths; Evelyn D. Taylor-Cox; Donald C. Behringer; Mark J. Butler; Richard F. Preziosi (Biodiversity and Conservation, 2020)
Genetic tools can have a key role in informing conservation management of declining populations. Genetic diversity is an important determinant of population fitness and resilience, and can require careful management to ensure sufficient variation is present. In addition, population genetics data reveal patterns of connectivity and gene flow between locations, enabling mangers to predict recovery and resilience, identify areas of local adaptation, and generate restoration plans. Here, we demonstrate a conservation genetics approach to inform restoration and management of the loggerhead sponge ( Spheciospongia vesparium ) in the Florida Keys, USA. This species is a dominant, habitat-forming component of marine ecosystems in the Caribbean region, but in Florida has suffered numerous mass mortality events. We developed microsatellite markers and used them to genotype sponges from 14 locations in Florida and a site each in The Bahamas, Belize and Barbuda. We found that genetic diversity levels were similar across all sites, but inbreeding and bottleneck signatures were present in Florida. Populations are highly structured at the regional scale, whilst within Florida connectivity is present in a weak isolation by distance pattern, coupled with chaotic genetic patchiness. Evidence of a weak barrier to gene flow was found in Florida among sites situated on opposite sides of the islands in the Middle Keys. Loggerhead sponge populations in Florida are vulnerable in the face of mass mortalities due to low connectivity with other areas in the region, as well as distance-limited and unpredictable local connectivity patterns. However, our discovery of Florida’s high genetic diversity increases hope for resilience to future perturbations. These results provide valuable insight for sponge restoration practice in Florida.

New GJA8 variants and phenotypes highlight its critical role in a broad spectrum of eye anomalies - Fabiola Ceroni; Domingo Aguilera-Garcia; Nicolas Chassaing; Dorine Arjanne Bax; Fiona Blanco-Kelly; Patricia Ramos; Maria Tarilonte; Cristina Villaverde; Luciana Rodrigues Jacy da Silva; Maria Juliana Ballesta-Martínez; Maria Jose Sanchez-Soler; Richard James Holt; et al. (Human Genetics, 2019)

Prospects and challenges of environmental DNA (eDNA) monitoring in freshwater ponds - Lynsey R. Harper; Andrew S. Buxton; Helen C. Rees; Kat Bruce; Rein Brys; David Halfmaerten; Daniel S. Read; Hayley V. Watson; Carl D. Sayer; Eleanor P. Jones; Victoria Priestley; Elvira Mächler; et al. (Hydrobiologia, 2019)

Climate and soils together regulate photosynthetic carbon isotope discrimination within C 3 plants worldwide - William K. Cornwell; Ian J. Wright; Joel Turner; Vincent Maire; Margaret M. Barbour; Lucas A. Cernusak; Todd Dawson; David Ellsworth; Graham D. Farquhar; Howard Griffiths; Claudia Keitel; Alexander Knohl; et al. (Global Ecology and Biogeography, 2018)
Aim Within C 3 plants, photosynthesis is a balance between CO 2 supply from the atmosphere via stomata and demand by enzymes within chloroplasts. This process is dynamic and a complex but crucial aspect of photosynthesis. We sought to understand the spatial pattern in CO 2 supply–demand balance on a global scale, via analysis of stable isotopes of carbon within leaves (Δ 13 C), which provide an integrative record of CO 2 drawdown during photosynthesis. Location Global Time period 1951–2011. Major taxa studied Vascular plants. Methods We assembled a database of leaf carbon isotope ratios containing 3,979 species–site combinations from across the globe, including 3,645 for C 3 species. We examined a wide array of potential climate and soil drivers of variation in Δ 13 C. Results The strongest drivers of carbon isotope discrimination at the global scale included atmospheric pressure, potential evapotranspiration and soil pH, which explained 44% of the variation in Δ 13 C. Addition of eight more climate and soil variables (each explaining small but highly significant amounts of variation) increased the explained variation to 60%. On top of this, the largest plant trait effect was leaf nitrogen per area, which explained 11% of Δ 13 C variation. Main conclusions: By considering variation in Δ 13 C at a considerably larger scale than previously, we were able to identify and quantify key drivers in CO 2 supply–demand balance previously unacknowledged. Of special note is the key role of soil properties, with greater discrimination on low‐pH and high‐silt soils. Unlike other plant traits, which show typically wide variation within sets of coexisting species, the global pattern in carbon stable isotope ratios is much more conservative; there is relatively narrow variation in time‐integrated CO 2 concentrations at the site of carboxylation among plants in a given soil and climate.

Practitioner and scientist perceptions of successful amphibian conservation - Helen M.R. Meredith; Freya A.V. St. John; Ben Collen; Simon A. Black; Richard A. Griffiths (Conservation Biology, 2018)
Conservation requires successful outcomes. However, success is perceived in many different ways depending on the desired outcome. Through a questionnaire survey, we examined perceptions of success among 355 scientists and practitioners working on amphibian conservation from over 150 organizations in more than 50 countries. We also sought to identify how different types of conservation actions and respondent experience and background influenced perceptions. Respondents identified 4 types of success: species and habitat improvements (84% of respondents); effective program management (36%); outreach initiatives such as education and public engagement (25%); and the application of science‐based conservation (15%). The most significant factor influencing overall perceived success was reducing threats. Capacity building was rated least important. Perceptions were influenced by experience, professional affiliation, involvement in conservation practice, and country of residence. More experienced practitioners associated success with improvements to species and habitats and less so with education and engagement initiatives. Although science‐based conservation was rated as important, this factor declined in importance as the number of programs a respondent participated in increased, particularly among those from less economically developed countries. The ultimate measure of conservation success—population recovery—may be difficult to measure in many amphibians; difficult to relate to the conservation actions intended to drive it; and difficult to achieve within conventional funding time frames. The relaunched Amphibian Conservation Action Plan provides a framework for capturing lower level processes and outcomes, identifying gaps, and measuring progress.

An evaluation of the hysteresis in chemical concentration–discharge ( C – Q ) relationships from drained, intensively managed grasslands in southwest England - Adebayo O. Eludoyin; Bruce Griffith; Robert J. Orr; Roland Bol; Timothy A. Quine; Richard E. Brazier (Hydrological Sciences Journal, 2017)

Telomere length measurement by qPCR in birds is affected by storage method of blood samples - Sophie Reichert; Hannah Froy; Winnie Boner; Theresa M. Burg; Francis Daunt; Robert Gillespie; Kate Griffiths; Sue Lewis; Richard A. Phillips; Dan H. Nussey; Pat Monaghan (Oecologia, 2017)

Modeling What We Sample and Sampling What We Model: Challenges for Zooplankton Model Assessment - Jason D. Everett; Mark E. Baird; Pearse Buchanan; Cathy Bulman; Claire Davies; Ryan Downie; Chris Griffiths; Ryan Heneghan; Rudy J. Kloser; Leonardo Laiolo; Ana Lara-Lopez; Hector Lozano-Montes; et al. (Frontiers in Marine Science, 2017)

A Galaxy-based bioinformatics pipeline for optimised, streamlined microsatellite development from Illumina next-generation sequencing data - Sarah M. Griffiths; Graeme Fox; Peter J. Briggs; Ian J. Donaldson; Simon Hood; Pen Richardson; George W. Leaver; Nathan K. Truelove; Richard F. Preziosi (Conservation Genetics Resources, 2016)

Discordance between morphological and taxonomic diversity: land snails of oceanic archipelagos - Kostas A. Triantis; François Rigal; Christine E. Parent; Robert A. D. Cameron; Bernd Lenzner; Aristeidis Parmakelis; Norine W. Yeung; María R. Alonso; Miguel Ibáñez; António M. de Frias Martins; Dinarte N. F. Teixeira; Owen L. Griffiths; et al. (Journal of Biogeography, 2016)
Aim Morphological and taxonomic diversity are intuitive measures of biological diversity. Previous studies have shown discordance between these measures at large spatial and temporal scales, but the implications of this pattern for the underlying processes are not understood. Using oceanic archipelagos as spatial units, we examine potential links between the morphological and taxonomic diversity of their land snail faunas in a biogeographical framework. Location Eleven major oceanic archipelagos. Methods For each archipelago, we assembled lists of indigenous land snail species, classified by family and genus, with shell height and width for each species (1723 species in total). We used biogeographic and climatic variables as potential predictors of diversity patterns. We employed regression analyses to evaluate (1) whether morphological diversity scales with taxonomic diversity at the species, genus or family level, and (2) whether morphological and taxonomic diversity correlate similarly with biogeographic/climatic factors. We also assessed which taxonomic level contributes most to morphological variation within archipelagos. Results Morphological diversity across archipelagos was strongly related to genus but not species richness. Within archipelagos, morphological variation reflected differences among genera and families but not species. Species richness was best explained by archipelago area, but morphological diversity was not significantly related to any of the physical features of archipelagos. Main conclusions Across archipelagos, species richness and morphological diversity of land snail faunas are decoupled. The relationship between species richness and the available ecological space (captured mainly by area) indicates the prevalence of niche‐based processes while, for morphological diversity, the strong conservatism of morphology at the genus level suggests the presence of diversification‐based limits. Assuming genera effectively reflect diversification, our findings indicate that morphological space on oceanic archipelagos depends primarily on the number of evolutionary units that have colonized and/or diversified through time.

Developments in amphibian captive breeding and reintroduction programs - Gemma Harding; Richard A. Griffiths; Lissette Pavajeau (Conservation Biology, 2016)
Captive breeding and reintroduction remain high profile but controversial conservation interventions. It is important to understand how such programs develop and respond to strategic conservation initiatives. We analyzed the contribution to conservation made by amphibian captive breeding and reintroduction since the launch of the International Union for Conservation of Nature (IUCN) Amphibian Conservation Action Plan (ACAP) in 2007. We assembled data on amphibian captive breeding and reintroduction from a variety of sources including the Amphibian Ark database and the IUCN Red List. We also carried out systematic searches of Web of Science, JSTOR, and Google Scholar for relevant literature. Relative to data collected from 1966 to 2006, the number of species involved in captive breeding and reintroduction projects increased by 57% in the 7 years since release of the ACAP. However, there have been relatively few new reintroductions over this period; most programs have focused on securing captive‐assurance populations (i.e., species taken into captivity as a precaution against extinctions in the wild) and conservation‐related research. There has been a shift to a broader representation of frogs, salamanders, and caecilians within programs and an increasing emphasis on threatened species. There has been a relative increase of species in programs from Central and South America and the Caribbean, where amphibian biodiversity is high. About half of the programs involve zoos and aquaria with a similar proportion represented in specialist facilities run by governmental or nongovernmental agencies. Despite successful reintroduction often being regarded as the ultimate milestone for such programs, the irreversibility of many current threats to amphibians may make this an impractical goal. Instead, research on captive assurance populations may be needed to develop imaginative solutions to enable amphibians to survive alongside current, emerging, and future threats.

Global change pressures on soils from land use and management - Pete Smith; Joanna I. House; Mercedes Bustamante; Jaroslava Sobocká; Richard Harper; Genxing Pan; Paul C. West; Joanna M. Clark; Tapan Adhya; Cornelia Rumpel; Keith Paustian; Peter Kuikman; et al. (Global Change Biology, 2016)
Soils are subject to varying degrees of direct or indirect human disturbance, constituting a major global change driver. Factoring out natural from direct and indirect human influence is not always straightforward, but some human activities have clear impacts. These include land‐use change, land management and land degradation (erosion, compaction, sealing and salinization). The intensity of land use also exerts a great impact on soils, and soils are also subject to indirect impacts arising from human activity, such as acid deposition (sulphur and nitrogen) and heavy metal pollution. In this critical review, we report the state‐of‐the‐art understanding of these global change pressures on soils, identify knowledge gaps and research challenges and highlight actions and policies to minimize adverse environmental impacts arising from these global change drivers. Soils are central to considerations of what constitutes sustainable intensification. Therefore, ensuring that vulnerable and high environmental value soils are considered when protecting important habitats and ecosystems, will help to reduce the pressure on land from global change drivers. To ensure that soils are protected as part of wider environmental efforts, a global soil resilience programme should be considered, to monitor, recover or sustain soil fertility and function, and to enhance the ecosystem services provided by soils. Soils cannot, and should not, be considered in isolation of the ecosystems that they underpin and vice versa. The role of soils in supporting ecosystems and natural capital needs greater recognition. The lasting legacy of the International Year of Soils in 2015 should be to put soils at the centre of policy supporting environmental protection and sustainable development.

Assessing the global zoo response to the amphibian crisis through 20‐year trends in captive collections - Jeff Dawson; Freisha Patel; Richard A. Griffiths; Richard P. Young (Conservation Biology, 2016)
Global amphibian declines are one of the biggest challenges currently facing the conservation community, and captive breeding is one way to address this crisis. Using information from the International Species Information System zoo network, we examined trends in global zoo amphibian holdings across species, zoo region, and species geographical region of origin from 1994 to 2014. These trends were compared before and after the 2004 Global Amphibian Assessment to assess whether any changes occurred and whether zoo amphibian conservation effort had increased. The numbers of globally threatened species (GTS) and their proportional representation in global zoo holdings increased and this rate of increase was significantly greater after 2004. North American, European, and Oceanian GTS were best represented in zoos globally, and proportions of Oceanian GTS held increased the most since 2004. South American and Asian GTS had the lowest proportional representation in zoos. At a regional zoo level, European zoos held the lowest proportions of GTS, and this proportion did not increase after 2004. Since 1994, the number of species held in viable populations has increased, and these species are distributed among more institutions. However, as of 2014, zoos held 6.2% of globally threatened amphibians, a much smaller figure than for other vertebrate groups and one that falls considerably short of the number of species for which ex situ management may be desirable. Although the increased effort zoos have put into amphibian conservation over the past 20 years is encouraging, more focus is needed on ex situ conservation priority species. This includes building expertise and capacity in countries that hold them and tracking existing conservation efforts if the evidence‐based approach to amphibian conservation planning at a global level is to be further developed.

Biodiversity and environmental context predict dung beetle‐mediated seed dispersal in a tropical forest field experiment - Hannah M. Griffiths; Julio Louzada; Richard D. Bardgett; Wallace Beiroz; Filipe França; Daniel Tregidgo; Jos Barlow (Ecology, 2015)
Biodiversity–ecosystem functioning (BEF) literature is dominated by investigations conducted in temperate grassland ecosystems under homogenous environmental conditions. Consequently, studies concerned with the functional importance of higher trophic levels, or with the role of environmental conditions in shaping BEF relationships, are comparatively uncommon. To address this, we assessed dung beetle diversity‐functioning relationships in situ, in a field experiment in the Brazilian Amazon. Dung beetles perform a number of ecological functions in habitats across the globe; in tropical forests they play a key role in the secondary dispersal of seeds. We therefore experimentally tested how the functional diversity of dung beetle communities affects seed dispersal and how BEF relationships varied with environmental context, by replicating the experiments under contrasting soil conditions. Relationships between dung beetle diversity and function were examined using diversity indices calculated using continuous morphological traits of the individuals involved in experiments, and functioning was measured as the dispersion of artificial seeds throughout the soil profile and the probability of burial. Ninety experimental plots were established across three distinct primary forest sites. We collected, identified, and measured almost 2000 beetles, and sieved around 11 Mg of soil to quantify the dispersion of 1800 seed mimics. There was a significant effect of dung beetle functional diversity on both seed dispersion and seed burial, although this depended on environmental context, with the strength or direction of responses differing across the contrasting soils. Regardless of soil type, functional richness, but not species richness, predicted seed dispersion. We therefore advocate the use of functional diversity indices over taxonomic approaches in dung beetle‐focused BEF investigations. Furthermore, we highlight the difficulties in generalizing BEF relationships, even considering a single function within the same ecosystem.

Successful eradication of invasive vertebrates on Rangitoto and Motutapu Islands, New Zealand - Richard Griffiths; Fin Buchanan; Keith Broome; John Neilsen; Derek Brown; Michelle Weakley (Biological Invasions, 2015)

Genetic evidence from the spiny lobster fishery supports international cooperation among Central American marine protected areas - Nathan K. Truelove; Sarah Griffiths; Kim Ley-Cooper; James Azueta; Isaias Majil; Stephen J. Box; Donald C. Behringer; Mark J. Butler; Richard F. Preziosi (Conservation Genetics, 2015)

Maximizing the phylogenetic diversity of seed banks - Kate E. Griffiths; Sharon T. Balding; John B. Dickie; Gwilym P. Lewis; Tim R. Pearce; Richard Grenyer (Conservation Biology, 2015)
Ex situ conservation efforts such as those of zoos, botanical gardens, and seed banks will form a vital complement to in situ conservation actions over the coming decades. It is therefore necessary to pay the same attention to the biological diversity represented in ex situ conservation facilities as is often paid to protected‐area networks. Building the phylogenetic diversity of ex situ collections will strengthen our capacity to respond to biodiversity loss. Since 2000, the Millennium Seed Bank Partnership has banked seed from 14% of the world's plant species. We assessed the taxonomic, geographic, and phylogenetic diversity of the Millennium Seed Bank collection of legumes (Leguminosae). We compared the collection with all known legume genera, their known geographic range (at country and regional levels), and a genus‐level phylogeny of the legume family constructed for this study. Over half the phylogenetic diversity of legumes at the genus level was represented in the Millennium Seed Bank. However, pragmatic prioritization of species of economic importance and endangerment has led to the banking of a less‐than‐optimal phylogenetic diversity and prioritization of range‐restricted species risks an underdispersed collection. The current state of the phylogenetic diversity of legumes in the Millennium Seed Bank could be substantially improved through the strategic banking of relatively few additional taxa. Our method draws on tools that are widely applied to in situ conservation planning, and it can be used to evaluate and improve the phylogenetic diversity of ex situ collections. Maximizar la Riqueza Filogenética de los Bancos de Semillas

Vegetation exerts a greater control on litter decomposition than climate warming in peatlands - Susan E. Ward; Kate H. Orwin; Nicholas J. Ostle; Maria J. I. Briones; Bruce C. Thomson; Robert I. Griffiths; Simon Oakley; Helen Quirk; Richard D. Bardgett (Ecology, 2015)
Historically, slow decomposition rates have resulted in the accumulation of large amounts of carbon in northern peatlands. Both climate warming and vegetation change can alter rates of decomposition, and hence affect rates of atmospheric CO 2 exchange, with consequences for climate change feedbacks. Although warming and vegetation change are happening concurrently, little is known about their relative and interactive effects on decomposition processes. To test the effects of warming and vegetation change on decomposition rates, we placed litter of three dominant species ( Calluna vulgaris , Eriophorum vaginatum , Hypnum jutlandicum ) into a peatland field experiment that combined warming with plant functional group removals, and measured mass loss over two years. To identify potential mechanisms behind effects, we also measured nutrient cycling and soil biota. We found that plant functional group removals exerted a stronger control over short‐term litter decomposition than did ~1°C warming, and that the plant removal effect depended on litter species identity. Specifically, rates of litter decomposition were faster when shrubs were removed from the plant community, and these effects were strongest for graminoid and bryophyte litter. Plant functional group removals also had strong effects on soil biota and nutrient cycling associated with decomposition, whereby shrub removal had cascading effects on soil fungal community composition, increased enchytraeid abundance, and increased rates of N mineralization. Our findings demonstrate that, in addition to litter quality, changes in vegetation composition play a significant role in regulating short‐term litter decomposition and belowground communities in peatland, and that these impacts can be greater than moderate warming effects. Our findings, albeit from a relatively short‐term study, highlight the need to consider both vegetation change and its impacts below ground alongside climatic effects when predicting future decomposition rates and carbon storage in peatlands.

Establishing the A. E. Watkins landrace cultivar collection as a resource for systematic gene discovery in bread wheat - Luzie U. Wingen; Simon Orford; Richard Goram; Michelle Leverington-Waite; Lorelei Bilham; Theofania S. Patsiou; Mike Ambrose; Jo Dicks; Simon Griffiths (Theoretical and Applied Genetics, 2014)

Vaccine immunotherapy for prostate cancer: from mice to men - David M. Lubaroff; Daniel Vaena; James A. Brown; Pamela Zehr; Karen C. Griffith; Erica Brown; Julie Eastman; Kenneth Nepple; Ambika Kattula; Richard D. Williams (Immunologic Research, 2014)

The importance of health co-benefits in macroeconomic assessments of UK Greenhouse Gas emission reduction strategies - Henning Tarp Jensen; Marcus R. Keogh-Brown; Richard D. Smith; Zaid Chalabi; Alan D. Dangour; Mike Davies; Phil Edwards; Tara Garnett; Moshe Givoni; Ulla Griffiths; Ian Hamilton; James Jarrett; et al. (Climatic Change, 2013)
We employ a single-country dynamically-recursive Computable General Equilibrium model to make health-focussed macroeconomic assessments of three contingent UK Greenhouse Gas (GHG) mitigation strategies, designed to achieve 2030 emission targets as suggested by the UK Committee on Climate Change. In contrast to previous assessment studies, our main focus is on health co-benefits additional to those from reduced local air pollution. We employ a conservative cost-effectiveness methodology with a zero net cost threshold. Our urban transport strategy (with cleaner vehicles and increased active travel) brings important health co-benefits and is likely to be strongly cost-effective; our food and agriculture strategy (based on abatement technologies and reduction in livestock production) brings worthwhile health co-benefits, but is unlikely to eliminate net costs unless new technological measures are included; our household energy efficiency strategy is likely to breakeven only over the long term after the investment programme has ceased (beyond our 20 year time horizon). We conclude that UK policy makers will, most likely, have to adopt elements which involve initial net societal costs in order to achieve future emission targets and longer-term benefits from GHG reduction. Cost-effectiveness of GHG strategies is likely to require technological mitigation interventions and/or demand-constraining interventions with important health co-benefits and other efficiency-enhancing policies that promote internalization of externalities. Health co-benefits can play a crucial role in bringing down net costs, but our results also suggest the need for adopting holistic assessment methodologies which give proper consideration to welfare-improving health co-benefits with potentially negative economic repercussions (such as increased longevity).

Priority research questions for the UK food system - John S. I. Ingram; Hugh L. Wright; Lucy Foster; Timothy Aldred; David Barling; Tim G. Benton; Paul M. Berryman; Charles S. Bestwick; Alice Bows-Larkin; Tim F. Brocklehurst; Judith Buttriss; John Casey; et al. (Food Security, 2013)
The rise of food security up international political, societal and academic agendas has led to increasing interest in novel means of improving primary food production and reducing waste. There are however, also many ‘post-farm gate’ activities that are critical to food security, including processing, packaging, distributing, retailing, cooking and consuming. These activities all affect a range of important food security elements, notably availability, affordability and other aspects of access, nutrition and safety. Addressing the challenge of universal food security, in the context of a number of other policy goals (e.g. social, economic and environmental sustainability), is of keen interest to a range of UK stakeholders but requires an up-to-date evidence base and continuous innovation. An exercise was therefore conducted, under the auspices of the UK Global Food Security Programme, to identify priority research questions with a focus on the UK food system (though the outcomes may be broadly applicable to other developed nations). Emphasis was placed on incorporating a wide range of perspectives (‘world views’) from different stakeholder groups: policy, private sector, non-governmental organisations, advocacy groups and academia. A total of 456 individuals submitted 820 questions from which 100 were selected by a process of online voting and a three-stage workshop voting exercise. These 100 final questions were sorted into 10 themes and the ‘top’ question for each theme identified by a further voting exercise. This step also allowed four different stakeholder groups to select the top 7–8 questions from their perspectives. Results of these voting exercises are presented. It is clear from the wide range of questions prioritised in this exercise that the different stakeholder groups identified specific research needs on a range of post-farm gate activities and food security outcomes. Evidence needs related to food affordability, nutrition and food safety (all key elements of food security) featured highly in the exercise. While there were some questions relating to climate impacts on production, other important topics for food security (e.g. trade, transport, preference and cultural needs) were not viewed as strongly by the participants.

Workshop on the ecosystem and fisheries of the Coral Sea: an Australian perspective on research and management - Jock W. Young; A. David McKinnon; Daniela Ceccarelli; Richard Brinkman; Rodrigo H. Bustamante; Mike Cappo; Cathy Dichmont; Peter Doherty; Miles Furnas; Daniel Gledhill; Shane Griffiths; Trevor Hutton; et al. (Reviews in Fish Biology and Fisheries, 2012)

Evidence for evolutionary distinctiveness of a newly discovered population of sooglossid frogs on Praslin Island, Seychelles - Michele L. Taylor; Nancy Bunbury; Lindsay Chong-Seng; Naomi Doak; Samit Kundu; Richard A. Griffiths; Jim J. Groombridge (Conservation Genetics, 2012)

Psilocybin occasioned mystical-type experiences: immediate and persisting dose-related effects - Roland R. Griffiths; Matthew W. Johnson; William A. Richards; Brian D. Richards; Una McCann; Robert Jesse (Psychopharmacology, 2011)

Fault Roughness at Seismogenic Depths from LIDAR and Photogrammetric Analysis - Andrea Bistacchi; W. Ashley Griffith; Steven A. F. Smith; Giulio Di Toro; Richard Jones; Stefan Nielsen (Pure and Applied Geophysics, 2011)

United States Pharmacopeia Safety Evaluation of Spirulina - Robin J. Marles; Marilyn L. Barrett; Joanne Barnes; Mary L. Chavez; Paula Gardiner; Richard Ko; Gail B. Mahady; Tieraona Low Dog; Nandakumara D. Sarma; Gabriel I. Giancaspro; Maged Sharaf; James Griffiths (Critical Reviews in Food Science and Nutrition, 2011)

Causes of arrested succession in coastal dune forest - Lauren J. Boyes; Richard M. Gunton; Megan E. Griffiths; Michael J. Lawes (Plant Ecology, 2011)

Ecological filtering by a dominant herb selects for shade tolerance in the tree seedling community of coastal dune forest - Zivanai Tsvuura; Megan E. Griffiths; Richard M. Gunton; Peter J. Franks; Michael J. Lawes (Oecologia, 2010)

Genes driving potato tuber initiation and growth: identification based on transcriptional changes using the POCI array - Bjorn Kloosterman; David De Koeyer; Rebecca Griffiths; Barry Flinn; Burkhard Steuernagel; Uwe Scholz; Sophia Sonnewald; Uwe Sonnewald; Glenn J. Bryan; Salomé Prat; Zsófia Bánfalvi; John P. Hammond; et al. (Functional & Integrative Genomics, 2008)

Captive Breeding, Reintroduction, and the Conservation of Amphibians - RICHARD A. GRIFFITHS; LISSETTE PAVAJEAU (Conservation Biology, 2008)
The global amphibian crisis has resulted in renewed interest in captive breeding as a conservation tool for amphibians. Although captive breeding and reintroduction are controversial management actions, amphibians possess a number of attributes that make them potentially good models for such programs. We reviewed the extent and effectiveness of captive breeding and reintroduction programs for amphibians through an analysis of data from the Global Amphibian Assessment and other sources. Most captive breeding and reintroduction programs for amphibians have focused on threatened species from industrialized countries with relatively low amphibian diversity. Out of 110 species in such programs, 52 were in programs with no plans for reintroduction that had conservation research or conservation education as their main purpose. A further 39 species were in programs that entailed captive breeding and reintroduction or combined captive breeding with relocations of wild animals. Nineteen species were in programs with relocations of wild animals only. Eighteen out of 58 reintroduced species have subsequently bred successfully in the wild, and 13 of these species have established self‐sustaining populations. As with threatened amphibians generally, amphibians in captive breeding or reintroduction programs face multiple threats, with habitat loss being the most important. Nevertheless, only 18 out of 58 reintroduced species faced threats that are all potentially reversible. When selecting species for captive programs, dilemmas may emerge between choosing species that have a good chance of surviving after reintroduction because their threats are reversible and those that are doomed to extinction in the wild as a result of irreversible threats. Captive breeding and reintroduction programs for amphibians require long‐term commitments to ensure success, and different management strategies may be needed for species earmarked for reintroduction and species used for conservation research and education.

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Psilocybin can occasion mystical-type experiences having substantial and sustained personal meaning and spiritual significance - R. R. Griffiths; W. A. Richards; U. McCann; R. Jesse (Psychopharmacology, 2006)

Introduced Alien or Persecuted Native? Resolving the Origin of the Viperine Snake (Natrix Maura) on Mallorca - Daniela Guicking; Richard A. Griffiths; Robin D. Moore; Ulrich Joger; Michael Wink (Biodiversity and Conservation, 2006)

Effects of Polyamine Synthesis Inhibitors on Primary Tumor Features and Metastatic Capacity of Human Breast Cancer Cells - Andrea Manni; Sharlene Washington; Xin Hu; James W. Griffith; Richard Bruggeman; Laurence M. Demers; David Mauger; Michael F. Verderame (Clinical & Experimental Metastasis, 2005)

Induced defences in an endangered amphibian in response to an introduced snake predator - Robin D. Moore; Richard A. Griffiths; Cliona M. O’Brien; Adam Murphy; David Jay (Oecologia, 2004)

Fluvial system response to Late Devensian (Weichselian) aridity, Baston, Lincolnshire, England - Rebecca M. Briant; G. Russell Coope; Richard C. Preece; David H. Keen; Steve Boreham; Huw I. Griffiths; Mary B. Seddon; Philip L. Gibbard (Journal of Quaternary Science, 2004)
Little is known about the impact of Late Devensian (Weichselian) aridity on lowland British landscapes, largely because they lack the widespread coversand deposits of the adjacent continent. The concentration of large interformational ice‐wedge casts in the upper part of many Devensian fluvial sequences suggests that fluvial activity may have decreased considerably during this time. The development of optically stimulated luminescence (OSL) dating enables this period of ice‐wedge cast formation to be constrained for the first time in eastern England, where a marked horizon of ice‐wedge casts is found between two distinctive dateable facies associations. Contrasts between this horizon and adjacent sediments show clear changes in environment and fluvial system behaviour in response to changing water supply, in line with palaeontological evidence. In addition to providing chronological control on the period of ice‐wedge formation, the study shows good agreement of the radiocarbon and OSL dating techniques during the Middle and Late Devensian, with direct comparison of these techniques beyond 15 000 yr for the first time in Britain. It is suggested that aridity during the Late Devensian forced a significant decrease in fluvial activity compared with preceding and following periods, initiating a system with low peak flows and widespread permafrost development. Copyright © 2004 John Wiley & Sons, Ltd.

Brood neglect and contingent foraging behavior in a pelagic seabird - Sue Lewis; Keith C. Hamer; Luisa Money; Richard Griffiths; Sarah Wanless; Thomas N. Sherratt (Behavioral Ecology and Sociobiology, 2004)

Primary sex ratios in birds: problems with molecular sex identification of undeveloped eggs - Kathryn E. Arnold; Kate J. Orr; Richard Griffiths (Molecular Ecology, 2003)
Sex allocation studies seek to ascertain whether mothers manipulate offspring sex ratio prior to ovulation. To do so, DNA for molecular sexing should be collected as soon after conception as possible, but instead neonates are usually sampled. Here, we aim to identify and quantify some of the problems associated with using molecular techniques to identify the sex of newly laid avian eggs. From both fertilized and unfertilized chicken ( Gallus gallus ) eggs, we sampled (1) the blastoderm/disc, (2) vitelline membrane and (3) a mixture of (1) and (2). Thus, we replicated scenarios under which contaminated samples are taken and/or unfertilized eggs are not identified as such and are sampled. We found that two commonly used molecular sexing tests, based on the CHD‐1 genes, differed in sensitivity, but this did not always predict their ability to sex egg samples. The vitelline membrane was a considerable source of maternal and probably paternal contamination. Fertile eggs were regularly assigned the wrong sex when vitelline membrane contaminated the blastoderm sample. The membrane of unfertilized eggs was always female, i.e. maternal DNA had been amplified. DNA was amplified from 47 to 63% of unfertilized blastodiscs, even though it was highly unlikely that DNA from a single haploid cell could be amplified reliably using these polymerase chain reaction (PCR) techniques. Surprisingly, the blastodiscs were identified as both males and females. We suggest that in these cases only maternal DNA was amplified, and that ‘false’ males, Z not ZZ, were detected. This was due to the reduced ability of both sets of primers to anneal to the W chromosome compared to the Z chromosome at low DNA concentrations. Overall, our data suggested that estimates of primary sex ratios based on newly laid eggs will be appreciably inaccurate.

Witches’ brooms and frosty pods: Two major pathogens of cacao - Gareth W. Griffith; Jean Nicholson; Anja Nenninger; Richard N. Birch; John N. Hedger (New Zealand Journal of Botany, 2003)
The agaric Crinipellis perniciosa (Tricholomataceae) is a hemibiotrophic pathogen which causes witches’ broom disease of cacao and has recently decimated the Brazilian cacao industry. In addition to the pathogenic cacao (C‐) biotype, other biotypes are found in association with unrelated plant taxa, notably bignoniaceous lianas (L‐biotype), solanaceous hosts (S ‐biotype), and the shrub Heteropterys acutifolia (H‐biotype). The C‐and S‐biotypes are non‐outcrossing and form broom symptoms on hosts, whereas the L‐biotype is outcrossing and asymptomatic. Phylogenetic analysis of several regions of the rRNA locus revealed near identity between C‐ and S‐biotype isolates from diverse locations, with the L‐ and H‐biotypes forming separate groupings. Preliminary analysis of sequence data from Moniliophthora roreri, causal agent of frosty pod disease, indicates that this morphologically distinct pathogen may be closely related to C. perniciosa. Similarities in host infection between C. perniciosa and M. roreri have previously been noted but it is difficult to reconcile the gross morphological differences. Pairings between C. perniciosa and M. roreri gave rise to a clamped dikaryotic mycelium suggestive of a hybridisation event.

Population dynamics of reintroduced forest birds on New Zealand islands - Doug P. Armstrong; R. Scott Davidson; Wendy J. Dimond; John K. Perrott; Isabel Castro; John G. Ewen; Richard Griffiths; Jason Taylor (Journal of Biogeography, 2002)
Aim We studied dynamics of four populations of New Zealand forest birds for 5–9 years after reintroduction to islands. We primarily aimed to predict whether these populations were viable, and what, if any, management was needed to maintain them. However, the small scale of these islands also provided an opportunity to study density‐dependent population growth over a short time frame. Location We studied New Zealand robin (toutouwai, Petroica australis ) and stitchbird (hihi, Notiomystis cincta ) populations reintroduced to Tiritiri Matangi, a 220‐ha offshore island near Auckland, and saddleback (tieke, Philesturnus carunculatus ) and stitchbird populations reintroduced to Mokoia, a 135‐ha island in Lake Rotorua. These islands are free of mammalian predators, but have highly modified habitat following clearing and regeneration. Methods We closely monitored each population, individually marking all or most of the birds and in some cases experimentally manipulated population density or food supply. We used model selection procedures to understand factors affecting survival, fecundity and dispersal, and developed stochastic simulation models. Results The Tiritiri Matangi robin and Mokoia saddleback populations grew without management and appear to be viable. Both showed strong evidence of density‐dependent growth, with fecundity (saddlebacks) and juvenile survival (both populations) declining with increasing density. Neither stitchbird population appears viable without management and supplementation experiments showed reproduction and/or survival to be limited by food supply. The Tiritiri Matangi population appears viable as long as supplementary feeding continues. However, the Mokoia population has a high mortality rate regardless of supplementary feeding, resulting in tenuous viability even with intensive management. Mokoia stitchbirds suffer from infection by Aspergillus fumigatus , a pathogenic fungus that is prevalent in highly modified habitats and more abundant on Mokoia than Tiritiri Matangi. Main conclusions Some forest birds can thrive in regenerating forest on islands and strong evidence of density dependence can be detected in such populations in as little as 5 years. This allows density‐dependent models to be developed, providing guidance when island populations are harvested for further translocations. Other species are limited by food supply in regenerating environments, a problem potentially overcome by management. However, prevalence of A. fumigatus may render highly modified environments uninhabitable by some species regardless of management.

Laying date and laying sequence influence the sex ratio of crimson rosella broods - Elizabeth Krebs; David Green; Michael Double; Richard Griffiths (Behavioral Ecology and Sociobiology, 2002)

Human vascular endothelial cells with extended life spans: In vitro cell response, protein expression, and angiogenesis - Edith Gagnon; Paola Cattaruzzi; May Griffith; Lea Muzakare; Katell LeFlao; Robert Faure; Richard Béliveau; Sabah N. Hussain; Michael Koutsilieris; Charles J. Doillon (Angiogenesis, 2002)

5,000 year-old spermatozoa in Quaternary Ostracoda (Crustacea) - Renate Matzke-Karasz; David Horne; Horst Janz; Huw Griffiths; William Hutchinson; Richard Preece (The Science of Nature, 2001)

The last wild Spix's Macaw and an Illiger's Macaw produced a hybrid - Cristina Y. Miyaki; Patricia J. Faria; Richard Griffiths; João C.C. Araujo; Yara M. Barros (Conservation Genetics, 2001)

Investigation of Building - Influenced Atmospheric Dispersion Using a Dual Source Technique - Ilias Mavroidis; Richard F. Griffiths (Environmental Monitoring and Assessment, 2000)

Components of the human spindle checkpoint control mechanism localize specifically to the active centromere on dicentric chromosomes - Richard Saffery; Danielle Irvine; Belinda Griffiths; Paul Kalitsis; K. Choo (Human Genetics, 2000)

The use of amplified fragment length polymorphism (AFLP) in the isolation of sex‐specific markers - RICHARD Griffiths; KATE Orr (Molecular Ecology, 1999)
Sex identification is a problem in research and conservation. It can often be solved using a DNA test but this is only an option if a sex‐specific marker is available. Such markers can be identified using the amplified fragment length polymorphism (AFLP) technique. This is usually a taxonomic method, as it produces a DNA fingerprint of 50–100 PCR bands. However, if male and female AFLP products are compared, sex‐specific markers are confined to the heterogametic sex and can rapidly be identified. Once a marker is found, AFLP can be used to sex organisms directly or the marker can be sequenced and a standard PCR test designed.

Continuous Blood Withdrawal as a Rapid Screening Method for Determining Clearance and Oral Bioavailability in Rats - W. Griffith Humphreys; Mary T. Obermeier; Richard A. Morrison (Pharmaceutical Research, 1998)

A DNA test to sex most birds - RICHARD GRIFFITHS; MIKE C. DOUBLE; KATE ORR; ROBERT J. G. DAWSON (Molecular Ecology, 1998)
Birds are difficult to sex. Nestlings rarely show sex‐linked morphology and we estimate that adult females appear identical to males in over 50% of the world's bird species. This problem can hinder both evolutionary studies and human‐assisted breeding of birds. DNA‐based sex identification provides a solution. We describe a test based on two conserved CHD (chromo‐helicase‐DNA‐binding) genes that are located on the avian sex chromosomes of all birds, with the possible exception of the ratites (ostriches, etc.; Struthioniformes). The CHD‐W gene is located on the W chromosome; therefore it is unique to females. The other gene, CHD‐Z, is found on the Z chromosome and therefore occurs in both sexes (female, ZW; male, ZZ). The test employs PCR with a single set of primers. It amplifies homologous sections of both genes and incorporates introns whose lengths usually differ. When examined on a gel there is a single CHD‐Z band in males but females have a second, distinctive CHD‐W band.